Activity report: Monitoring Outcome of Climate-Smart Agriculture in Kaffrine ClimateSmart Village, Senegal - Ouédraogo, Mathieu; Fall, Mamadou; Adeyemi, Chabi (2020)
A Climate-Smart Village (CSV) monitoring survey was carried out in Senegal from 14 to 24 November, 2019 by CCAFS WA and CCAFS/CIAT team. Prior to the survey, a one-week training workshop was organized in Kaffrine, from 8 to 13 November 2019 to build the capacities of the local implementation team. The main objective of the CSV monitoring was to assess farmers’ adoption/implementation of Climate-Smart Agricultural (CSA) practices and technologies over the last 12 months and the perceived effects of their implementation on: food security and diversity, crops productivity and income, adaptive capacity and gender aspects (labour, participation in decision making, access/control over generated resources). Seven promising CSA options were considered. Those options included: tree planting, farmer managed natural regeneration, drought tolerant improved varieties of millet, maize or groundnut , reduced tillage, manure use combined with microdose of inorganic fertilizer of NPK and urea, microdose of inorganic fertilizer of NPK and urea and organic fertilizer only (manure, compost). The CSV monitoring targeted two adult persons of opposite sex involved in on-farm activities from a sample of 191 household located in ten villages within the Kaffrine CSV site. The surveyed villages included: Fass Sy (01), Mbane (02), Touba Taba (03), Toune Mosquée (04), Medina Ndiognick (05), Ngouye (06), Ndamboul Mboul (07), Touba Keur Cheikh (08), Djida (09), Daga-Birame (10). Households from Daga-Birame are direct beneficiaries of the CCAFS led CSV activities while the ones located in the other villages are considered non-beneficiaries or “additional”. The monitoring survey covered 378 individual farmers: 191 males and 187 females.